2018
DOI: 10.2196/games.9231
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Cue Refusal Video Game for Alcohol and Cigarette Recovery Support: Summative Study

Abstract: BackgroundNew technologies such as virtual reality, augmented reality, and video games hold promise to support and enhance individuals in addiction treatment and recovery. Quitting or decreasing cigarette or alcohol use can lead to significant health improvements for individuals, decreasing heart disease risk and cancer risks (for both nicotine and alcohol use), among others. However, remaining in recovery from use is a significant challenge for most individuals.ObjectiveWe developed and assessed the Take Cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…VR exposure therapies have been shown to be effective in the treatment of a variety of conditions including: specific phobias (acrophobia, aviophobia, arachnophobia), social anxiety disorder, public speaking anxiety, panic disorder, posttraumatic stress disorder, acute stress disorder, substance abuse disorders (alcohol and nicotine), and depression (26)(27)(28)(29)(30). A number of studies have been published on the use of immersive VR by healthy older adults (31,32), but very few have empirically examined the feasibility of introducing immersive VR in rehab or long-term care settings (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…VR exposure therapies have been shown to be effective in the treatment of a variety of conditions including: specific phobias (acrophobia, aviophobia, arachnophobia), social anxiety disorder, public speaking anxiety, panic disorder, posttraumatic stress disorder, acute stress disorder, substance abuse disorders (alcohol and nicotine), and depression (26)(27)(28)(29)(30). A number of studies have been published on the use of immersive VR by healthy older adults (31,32), but very few have empirically examined the feasibility of introducing immersive VR in rehab or long-term care settings (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly healthcare providers and caregivers are using virtual reality (VR) simulation as one approach to enhance empathic understanding for training and educational purposes (Aziz, 2018;Dyer, Swartzlanfer, & Gugliucci, 2018;Jütten et al, 2017;Elliman, Loizou, & Loizides, 2016;McDougall, 2015). VR has been used for a range of conditions, for example, alcoholism (Metcalf, Rossie, Stokes, Tallman, & Tanner, 2018), multiple sclerosis (Massetti et al, 2016), cardiovascular disease (Silva, Southworth, Raptis, & Sliva, 2018) and dementia (Wijma et al, 2018).…”
mentioning
confidence: 99%
“…Indeed-despite a single treatment sessionparticipants changed implicit craving (as assessed via alcohol implicit association test, eye-tracking test and alcohol Stroop test) as well as explicit, self-reported craving. Metcalf et al developed a serious game in VR for individuals with alcohol and nicotine dependence (n = 61) with the aim to strengthen refusal of addiction-related cues [41]. Specifically, users were instructed to hit or kick away drug-related cue images as they fly towards the user.…”
Section: Vr-based Therapeutic Approachesmentioning
confidence: 99%
“…A different therapeutic approach used a virtual reality game where participants crushed virtual cigarettes with their arm motion [41,53]. By using this approach, Girard et al found no significant effect on nicotine abstinence for the cigarettes crushing group (n = 46) compared to a placebo virtual condition (n = 45) after 4 weeks of treatment [53].…”
Section: Vr-based Therapeutic Approachesmentioning
confidence: 99%